2017
DOI: 10.1111/codi.13403
|View full text |Cite
|
Sign up to set email alerts
|

Symptom load and individual symptoms before and after repair of parastomal hernia: a prospective single centre study

Abstract: Aim The symptom load and individual symptoms before and after repair of parastomal hernia were investigated.Method Stoma-related symptoms were prospectively recorded before repair of a parastomal hernia and at 10 days and 6 months postoperatively: leakage, skin problems, difficulty with the appliance, limitation of activity, difficulty with clothing, cosmetic complaints, social restriction, erratic action of the stoma, a bearingdown sensation at the site of the stoma and pain. Episodes of intermittent bowel ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 36 publications
0
29
0
Order By: Relevance
“…Purposeful sampling ensured variation in experienced symptoms (Polit & Beck, ). We recruited patients referred to repair of parastomal bulging as they were assessed to have symptomatic bulging (Krogsgaard et al., ). Furthermore, we included patients receiving nonsurgical treatment who reported less symptomatic or even symptomless bulging (Moreno‐Matias et al., ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Purposeful sampling ensured variation in experienced symptoms (Polit & Beck, ). We recruited patients referred to repair of parastomal bulging as they were assessed to have symptomatic bulging (Krogsgaard et al., ). Furthermore, we included patients receiving nonsurgical treatment who reported less symptomatic or even symptomless bulging (Moreno‐Matias et al., ).…”
Section: Methodsmentioning
confidence: 99%
“…• Establishing a patient perspective in parastomal bulging is important to improve clinical outcome. KROGSGAARD ET AL. | 5073 appliance leakage (Cowin & Redmond, 2012;Krogsgaard et al, 2017;Ripoche, Basurko, Fabbro-Perray, & Prudhomme, 2011), skin problems (Cowin & Redmond, 2012;Krogsgaard et al, 2017;Ripoche et al, 2011;Rubin & Bailey, 1993;Wara & Andersen, 2011), pain Ripoche et al, 2011;Rubin & Bailey, 1993;Wara & Andersen, 2011), difficulty with ostomy appliance (Cowin & Redmond, 2012;Krogsgaard et al, 2017;Ripoche et al, 2011;Rubin & Bailey, 1993;Wara & Andersen, 2011), a bearing-down sensation at the site of the stoma (Cowin & Redmond, 2012;Krogsgaard et al, 2017), limitation of activity Rubin & Bailey, 1993), difficulty with clothing and cosmetic complaints Ripoche et al, 2011). While each of the latter six symptoms was reported in more than 50% of patients referred to surgical treatment , a French survey found that 24% of patients had no "particular problems" (Ripoche et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…In the generic C-30, patients with a PSH reported a greater problem with constipation. Pain is a major symptom of PSH [10], and one could speculate that opioid treatment with secondary constipation played a part in this difference. Previous results published by our research group showed that stoma patients with a PSH or bulge reported inferior scores in several symptom and functional scales [3].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have described problems such as social restriction, difficulty in stoma dressing, appliance leakage, pain, limitations of activity, cosmetic problems, and difficulties with clothing [10][11][12]. If a PSH or bulge is present, the patient's quality of life is reduced even more [3].…”
Section: Introductionmentioning
confidence: 99%
“…When reversed, these effects seem to be reduced and the global quality of life (QoL) seems to improve [16]. Patients with a permanent stoma have generally been found to have a lower QoL but also problems with pain, skin excoriation, and leakage [17,18]. Failure to reverse a defunctioning ileostomy after rectal cancer surgery is counter to the fundamental purpose of preserving the sphincter at the index operation.…”
Section: Introductionmentioning
confidence: 99%